RELEVANSI INDIKATOR KEUANGAN DENGAN METODE GENERAL PRICE LEVEL ACCOUNTING DAN CURRENT COST ACCOUNTING - Vita Indriyani, Ni Made; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2015)
PSAK 63 describes the restatement of Historical Cost reports are presented at the end of the period using the unit of measurement at fair value. The purpose of research to determine the difference in value of financial indicators of general price level accounting and historical cost accounting, the difference in value of financial indicators of current cost accounting and historical cost accounting. The study was conducted in the consumer goods industry sub-sectors of food and beverages totaling 15 samples, purposive sampling and analysis techniques the Wilcoxon test different. Based on the analysis, there is a difference between value financial indicators of general price level accounting and historical cost accounting and there is a difference between value financial indicators of current cost accounting and historical cost accounting.
Keywords: financial indicators, historical cost accounting, general price level accounting, current cost accounting, inflation